Designing Sign System in Sirah Kencong Blitar as A Tourists Information Media - Pracakaputra, Rezkyanori Novembra Pramadhani; Kusumasari, Adita Ayu (LPPM STIKI Malang, 2024)
Blitar Regency, which is located in East Java Province, offers interesting natural and cultural riches. According to Detik Travel, as of April 2023, there are 35 tourist attractions that attract the attention of visitors, making Blitar a popular destination. One of them is Sirah Kencong, a tourist area with unique advantages. However, the current sign system is still traditional and less effective in providing clear guidance to visitors. By applying visual communication design and semiotic theory, this redesign is expected to improve navigation, provide more complete information, and increase a satisfying tourist experience. Significant visit data shows the need to improve information infrastructure to support sustainable tourism growth. It is hoped that the implementation of an innovative, consistent and inclusive sign system can optimize the natural tourism potential of Sirah Kencong by presenting clear information and supporting the overall visitor experience.